The Relationship Between Physical Activity and Asthma Control in the Elderly - Ainil, Ainil Aulia Hasanah; Herlina (Indonesian Journal of Health Research and Development, 2025)
Background of study: Asthma is a chronic respiratory disease often experienced by the elderly, characterized by inflammation and narrowing of the airways. Good asthma control is important to prevent recurrence. Physical activity contributes to improving lung function and reducing inflammation, thus helping to better control asthma.Aims and scope: identify the relationship between physical activity and asthma control in the elderly.Method: This research is quantitative using descriptive correlation and cross-sectional approaches. The sample of this study had 58 respondents at Puskesmas Rawat Inap Simpang Tiga and Puskesmas Rejosari who used purposive sampling technique. Data were collected using two questionnaires, the Physical Activity Scale for the Elderly (PASE) to assess physical activity levels and the Asthma Control Test (ACT) to evaluate asthma control. Data were analyzed by univariate and bivariate analysis using Chi-square test.Results: The majority of respondents had heavy physical activity as many as 39 people (67.2%), and light physical activity as many as 19 people (32.8%), and uncontrolled asthma as many as 40 people (69%) and partially controlled asthma as many as 18 people (31%). The results of statistical tests showed a relationship between physical activity and asthma control in the elderly with a p-value of 0.029 < 0.05.Conclusion: The heavier the intensity of physical activity, such as intense exercise, heavy physical labor, or fast running, the more difficult it is for the elderly to control asthma. In contrast, light physical activity is more recommended as it has the potential to support better asthma control.